Employee Performance in Improving Public Services at the Puskesmas Ueesi District, East Kolaka Regency - Selmawati; Maulid; Zahari, Ahmad Farouq Mulku (Teras Kampus, 2025)
This study aims to determine employee performance in improving public services at the community health center (Puskesmas) in Ueesi District, East Kolaka Regency by using five main indicators, namely: productivity, service quality, responsiveness, responsibility, and accountability. The research method used in this study is qualitative and descriptive. The data used are sourced from primary data collected directly, as well as secondary data from related documents. The data collection techniques include interviews, observation, and documentation. Furthermore, the data is analyzed through stages of analysis that include data collection, reduction, presentation, and drawing conclusions. Informants in this study consisted the head of Puskesmas, staff, and community service users. The results of the study indicate that staff have shown increased productivity, as they continue to strive to provide optimal service despite limited facilities. Service quality still faces challenges such as waiting times and queuing systems. Staff responsiveness is quite good, demonstrated by their ability to adapt services to local needs, including emergency situations. Tasks are carried out in accordance with Standard Operating Procedures (SOPs), reflecting good responsibility, despite the dilemma of balancing regulations and patient needs. Public accountability has begun to be implemented through community involvement and regular reporting to the Health Office. Overall, the performance of staff at the Puskesmas Ueesi District is considered quite good, but still requires continuous improvement to achieve optimal and equitable health services.